Monte Carlo Comparison of the Methods for Estimating the Weibull Distribution Parameters – Wind Speed Application - Ivana Pobocikova; Zuzana Sedliackova; Maria Michalkova; Florence George (Communications - Scientific letters of the University of Zilina, 2017)
Wind energy is considered one of the most significant alternative energy sources for electrical energy production. The most important factor for modelling wind energy is the wind speed. The two-parameter Weibull distribution is commonly used for modelling wind speed. Its parameters play an important role in the wind energy applications and so it is important to choose the best method for the estimation of these parameters. In this paper we investigate and compare six different methods for estimating the Weibull distribution parameters. The methods we considered are the maximum likelihood method, the method of moments, the empirical method, the power density method, the least squares method and the weighted least squares method. The performance of these methods is compared and discussed through the Monte Carlo simulation.